2009
DOI: 10.1063/1.3068415
|View full text |Cite
|
Sign up to set email alerts
|

Computing the Jones index of quadratic permutation endomorphisms of O2

Abstract: We compute the index of the inclusions of type III 1/2 factors arising from endomorphisms of the Cuntz algebra O 2 associated to the rank-two permutation matrices.MSC 2000: 46L37, 46L05

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Hence k i = 0 for all i and thus X (k) z = 1. Now, identity (5) implies that U * v k is fixed by the gauge action and hence belongs to F n . Now, we are ready to prove the second main result of this paper.…”
Section: The Relative Commutantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence k i = 0 for all i and thus X (k) z = 1. Now, identity (5) implies that U * v k is fixed by the gauge action and hence belongs to F n . Now, we are ready to prove the second main result of this paper.…”
Section: The Relative Commutantsmentioning
confidence: 99%
“…But it can be shown that λ u is irreducible on O 2 (e.g., see [5], where this endomorphism is denoted ρ 142 ), and hence λ u (O 2 ) ′ ∩O 2 = C1. Thus h is a scalar and consequently Ad u • ϕ is identity on λ u (F 2 ) ′ ∩ O 2 .…”
Section: The Relative Commutantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Permutative endomorphisms of graph C * -algebras and especially of the Cuntz algebras O n have already received considerable attention and have been studied in several different contexts. In particular, localized endomorphisms (a class of endomorphisms that includes permutative ones) of the Cuntz algebras were investigated in the framework of the Jones index theory in [16,22,6,8,7,14]. Similar investigations of localized endomorphisms of the Cuntz-Krieger algebras were carried out in [17].…”
Section: Introductionmentioning
confidence: 99%
“…We adopt the same notation as in [CS09], where the monomial s i s j s * k is denoted by s ij,k . The following table displays not only the definitions of the endomorphisms we are going to consider but also says in advance which ones extend and which ones do not extend.…”
mentioning
confidence: 99%